Phylogeography of Kandelia candel in East Asiatic mangroves based on nucleotide variation of chloroplast and mitochondrial DNAs - Chiang, T.Y. (Wiley, 2019)
Vivipary with precocious seedlings in mangrove plants was thought to be a hindrance to long‐range dispersal. To examine the extent of seedling dispersal across oceans, we investigated the phylogeny and genetic structure among East Asiatic populations of Kandelia candel based on organelle DNAs. In total, three, 28 and seven haplotypes of the chloroplast DNA (cpDNA) atpB‐rbcL spacer, cpDNA trnL‐trnF spacer, and mitochondrial DNA (mtDNA) internal transcribed spacer (ITS) were identified, respectively, from 202 individuals. Three data sets suggested consistent phylogenies recovering two differentiated lineages corresponding to geographical regions, i.e. northern South‐China‐Sea + East‐China‐Sea region and southern South‐China‐Sea region (Sarawak). Phylogenetically, the Sarawak population was closely related to the Ranong population of western Peninsula Malaysia instead of other South‐China‐Sea populations, indicating its possible origin from the Indian Ocean Rim. No geographical subdivision was detected within the northern geographical region. An analysis of molecular variance (amova) revealed low levels of genetic differentiation between and within mainland and island populations (ΦCT = 0.015, ΦSC = 0.037), indicating conspicuous long‐distance seedling dispersal across oceans. Significant linkage disequilibrium excluded the possibility of recurrent homoplasious mutations as the major force causing phylogenetic discrepancy between mtDNA and the trnL‐trnF spacer within the northern region. Instead, relative ages of alleles contributed to nonrandom chlorotype–mitotype associations and tree inconsistency. Widespread distribution and random associations (χ2 = 0.822, P = 0.189) of eight hypothetical ancestral cytotypes indicated the panmixis of populations of the northern geographical region as a whole. In contrast, rare and recently evolved alleles were restricted to marginal populations, revealing some preferential directional migration.